Optimizing performance in sport: An action-based perspective - Carson, H.; Robazza, C.; Collins, D.; Toner, J.; Bertollo, M. (Advances in mental skills training, 2021)
Athletes are often required to execute motor skills under conditions of com-petitive pressure. Consequently, achieving and maintaining high levels of performance under dynamic, stressful, and demanding situations is an essential characteristic of successful performance (Collins & Kamin, 2012; Swann, Keegan, Crust, & Piggott, 2016). Indeed, the provision of services to achieve such outcomes has been a longstanding and primary purpose of performance sport psychology (Moran & Toner, 2017). Future research should employ longitudinal interventions to examine the effect of the recommendations provided above, aimed at improving performances under pressure. We suggest that such undertaking be conducted on an intraindividual basis (e.g., Carson & Collins, 2015) to acknowledge the idio-syncratic nature of motor representations. Interventions should combine existing precepts of the MAP, detailed guidelines for constructing imagery scripts (e.g., PETTLEP; Holmes & Collins, 2001), the development of metacognitive skills (e.g., reflection within an activity to evaluate and adjust cognitions, and judgments of learning) to recognize and regulate psychoemotional states ( MacIntyre, Igou, Campbell, Moran, & Matthews, 2014), and practice variables to target increased confidence and embedding of the skill to LTM. The role of athlete understanding is another key factor worthy of more attention. For applied purposes, it is important to consider the relationship between psychology and motor control domains, thereby integrating more "mental-focused" perspectives with actionbased approaches to performance improvement and optimization.